Associations between dietary coenzyme Q10 intake and lipid profiles in adults: a national cross-sectional study - Zhao, Mingzhu; Tian, Zezhong; Zhao, Dan; Kuang, Huiying; Liang, Ying; Liu, Zhihao; Xu, Yixuan; Hou, Shanshan; Zhong, Zepei; Yang, Yan (Frontiers in Nutrition, 2024)
Objective This study aimed to determine the average intake of CoQ10 from dietary sources and explore the dose–response relationships between the dietary-derived CoQ10 intake and lipid profiles. Methods We performed a cross-sectional study based on the China Health and Nutrition Survey, which included 7,938 adults. The dietary intake assessment used three consecutive 24-h recalls combined with a household inventory. Serum was used for lipid profiling. Results The average dietary-derived CoQ10 intake was 5.4 mg/day in Chinese adults. The dietary CoQ10 intake of the highest quartile (Q4 ≥ 6.96 mg/day) was negatively associated with total cholesterol (TC) [−0.12 (−0.19, −0.06) mmol/L], low-density lipoprotein cholesterol (LDL-C) [−0.17 (−0.23, −0.10) mmol/L], and non-high-density lipoprotein cholesterol (non-HDL-C) [−0.12 (−0.18, −0.05) mmol/L], while positively associated with apolipoprotein A-1 (ApoA1) [0.10 (0.08, 0.13) g/L] and triglycerides (TG) [0.14 (0.05, 0.23) mmol/L], compared to the lowest quartile (Q1 < 1.88 mg/day). Besides, dietary CoQ10 intake showed nonlinear dose–response associations with the above lipid variables (all Pnonlinear < 0.05). Conclusion Dietary-derived CoQ10 intake may be associated with some lipid profiles, such as TG, ApoA1, TC, LDL-C, and non-HDL-C. However, CoQ10 from dietary sources may not be a good choice for individuals who need to CoQ10 supplement.